2018
DOI: 10.1145/3196276
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Complexity of Layout Parameters in Tournaments and Semicomplete Digraphs

Abstract: A simple digraph is semi-complete if for any two of its vertices u and v, at least one of the arcs (u, v) and (v, u) is present. We study the complexity of computing two layout parameters of semi-complete digraphs: cutwidth and optimal linear arrangement (Ola). We prove that:• Both parameters are NP-hard to compute and the known exact and parameterized algorithms for them have essentially optimal running times, assuming the Exponential Time Hypothesis. • The cutwidth parameter admits a quadratic Turing kerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…due to Fradkin [18] for computing the cutwidth of a tournament. Barbero et al [4] showed that Fradkin's approach in [18] yields a polynomial time algorithm for the Optimal Linear Arrangement problem on tournaments as well. We rely on the analysis of Barbero et al in [4] to conclude that Fradkin's approach works for Minimum Directed Bisection on tournaments as well.…”
Section: :3mentioning
confidence: 99%
See 3 more Smart Citations
“…due to Fradkin [18] for computing the cutwidth of a tournament. Barbero et al [4] showed that Fradkin's approach in [18] yields a polynomial time algorithm for the Optimal Linear Arrangement problem on tournaments as well. We rely on the analysis of Barbero et al in [4] to conclude that Fradkin's approach works for Minimum Directed Bisection on tournaments as well.…”
Section: :3mentioning
confidence: 99%
“…Barbero et al [4] showed that Fradkin's approach in [18] yields a polynomial time algorithm for the Optimal Linear Arrangement problem on tournaments as well. We rely on the analysis of Barbero et al in [4] to conclude that Fradkin's approach works for Minimum Directed Bisection on tournaments as well. We establish the NP-hardness of Minimum Directed Bisection on semicomplete digraphs by a reduction from the Maximum Bisection problem on directed acyclic graphs.…”
Section: :3mentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the power of Turing kernelization is one of the main open research horizons in parameterized algorithmics. There is a handful of problems for which a nontrivial Turing kernelization is known [1,3,4,6,14,17,19,20,26,28]. On the other hand, there is a hierarchy of parameterized complexity classes which are conjectured not to admit polynomial Turing kernels [16].…”
Section: Introductionmentioning
confidence: 99%